Orson Welles – banda de um homem só - Esteves, Leonardo (Imagofagia, 2021)
Sobre Müller, Adalberto. Orson Welles – banda de um homem só. Rio de Janeiro: Azougue Editorial, 2015, 128pp., ISBN: 9788579201820.